Digital repositories and knowledge networks - Ismail, Saidatul Akmar (2008)
Digital technologies require new values, attitudes and patterns of behavior to access information.Their existence will not be successful and viable, if the systems are not accepted, utilized effectively and shared systematically.In Malaysian IHE ,the development of digital repositories is encouraging.All academic libraries are making full use of their websites to archive and post their institutional resources. Therefore, the main purpose of this paper is to highlight the importance of digitization of research output in a shareable way.The interactivity and knowledge networking environments can be accelerated through the interoperability principle in the development of digital repositories.